In Vitro and In Vivo Effects of Adrenaline and Phentolamine on Platelet Function - Ponari, Oreste; Civardi, Emilio; Megha, Alessandro; Pini, Mario; Poti’, Raffaele; Dettori, Anton Giulio (Thrombosis and Haemostasis, 1978)
In vitro and in vivo effects of adrenaline (ADR) on platelet aggregation, on platelet factor 3 (PF3) availability and on platelet factor 4 (PF4) release were studied in man. Inhibitory action of an alpha-blocker, phentolamine (PHEN) was investigated in the same conditions.The threshold concentration (TC) of ADR inducing the typical two-phase response in aggregation tests when added to platelet-rich plasma (PRP) varied in different pools of plasma, but always induced an evident PF4 release and increased PF3 availability. A further increase in both parameters was obtained with higher concentrations but without any significant dose/response correlation.Adding PHEN alone to PRP did not induce platelet aggregation or modify PF4 release induced by stirring, but it reduced PF3 availability. On the other hand, PHEN prevented the effects of ADR in different platelet tests, at appropriate concentrations.Intravenous infusion of ADR lowered the TC, and increased PF3 availability and PF4 release. In vivo administration of PHEN, in contrast, increased TC and reduced PF3 availability, while PF4 remained unchanged.